Application of starch degrading bacteria from tobacco leaves in improving the flavor of flue-cured tobacco - Gong, Yinuo; Li, Jingjing; Deng, Xiaohua; Chen, Yiqiang; Chen, Shanyi; Huang, Hemin; Ni, Li; Long, Teng; He, Wei; Zhang, Jianping; Jiang, Zhenkun; Fan, Jianqiang; et al. (Frontiers in Microbiology, 2023)
Starch is an essential factor affecting the quality of flue-cured tobacco, and high starch content can affect the sensory quality and safety. Recently, the degradation of macromolecules in tobacco raw materials by using additional microorganisms to improve their intrinsic quality and safety has become a new research hotspot in the tobacco industry. However, the technical maturity and application scale are limited. Our study analyzed the correlation between microbial community composition and volatile components on the surface of tobacco leaves from 14 different grades in Fujian tobacco-producing areas. The PICRUSt software was utilized to predict the function of the microbial community present in tobacco leaves. Furthermore, dominant strains that produced amylase were screened out, and an enzyme solution was prepared to enhance the flue-cured tobacco flavor. Changes in the content of macromolecules and volatile components were determined, and sensory evaluations were conducted to assess the overall quality of the tobacco leaves. The results showed that the dominant bacterial genera on the surface of Fujian tobacco leaves were Variovorax, Sphingomonas, Bacillus, etc. Bacillus was positively correlated with various volatile components. The main genetic functions of Fujian flue-cured tobacco surface bacteria were carbohydrate metabolism. After treating flue-cured tobacco with an enzyme preparation of Paenibacillus amylolyticus A17 #, the content of starch, pectin, and cellulose decreased significantly. Meanwhile, the content of total soluble sugar and reducing sugar was significantly increased, and the volatile aroma components, such as ethyl palmitate, ethyl linolenic acid, etc., were significantly increased. The aroma quality of flue-cured tobacco were enhanced. The taste characteristics were improved. Bacillus, the dominant genus in the abundance of bacterial communities on tobacco surfaces in Fujian, had an essential impact on the flavor of tobacco leaves by participating in carbohydrate metabolism and finally forming the unique flavor style of flue-cured tobacco. Paenibacillus amylolyticus A17 #, a target strain with amylase-producing ability, was screened from the surface of Fujian flue-cured tobacco. The enzyme preparation of Paenibacillus amylolyticus A17 #, was utilized to reduce the content of macromolecules, and produce a variety of crucial volatile aroma components, which had a significant improvement on the quality of tobacco leaves.